The Role of Organizational Commitment as a Mediator in Work-Family Conflict and Organizational Culture on Turnover Intention - Bekti Divayani, Naelin Dinda; Darmawan, Akhmad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The research method is non-probability sampling using a saturation sampling approach. A total of 280 non-medic employees from Purwokerto Privat Hospital participated as respondents in this study. Data collection was conducted through a questionnaire using the Likert scale to measure statement items related to the research variables. Data analysis utilized the SEM-PLS method, which is divided into two stages: an outer model evaluation to measure validity and reliability, and a structural model evaluation to test hypotheses and explain the relationships between variables. Results of this study states that work-family conflict has a positive effect on turnover intention, while organizational culture and organizational commitment have a negative and significant relationship with turnover intention. In addition, it was found that organizational commitment acts as mediator, connecting work-family conflict and organizational culture with turnover intentation. This research aims to provide a deeper understanding of how the conflict between work and family influences the desire to change jobs, with Organizational Culture as a factor that may alleviate its negative impact. Additionally, the study will elucidate the role of Organizational Commitment as a mediator in this relationship. It is expected that the findings of this research will offer insights to organizations in developing more targeted strategies to enhance employee well-being and reduce turnover rates, aligning with the long-term vision of organizational sustainability. Keywords: Organizational Commitment; Work-Family Conflict; Organizational culture; Turnover Intention